2011
DOI: 10.1002/hbm.21234
|View full text |Cite
|
Sign up to set email alerts
|

Challenging a decade of brain research on task switching: Brain activation in the task‐switching paradigm reflects adaptation rather than reconfiguration of task sets

Abstract: In daily life, we permanently need to adapt our behavior to new task situations, requiring cognitive control. Such adaptive processes are commonly investigated with the task-switching paradigm. Many fMRI studies have interpreted stronger activation for switch than repeat trials in fronto-parietal brain areas as reflecting an active reconfiguration process in switch trials, tuning the cognitive system for proper task execution. From the single cell literature, however, one could deduce the alternative interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 79 publications
6
24
1
Order By: Relevance
“…We found longer response times (RT) in switch trials compared to repeat trials, and with short CSI compared to long CSI, replicating findings of earlier studies [9], [13], [35]. Similar effects of switch trials and short CSI were found in ERPs.…”
Section: Discussionsupporting
confidence: 88%
“…We found longer response times (RT) in switch trials compared to repeat trials, and with short CSI compared to long CSI, replicating findings of earlier studies [9], [13], [35]. Similar effects of switch trials and short CSI were found in ERPs.…”
Section: Discussionsupporting
confidence: 88%
“…In studies of human perception, many cortical areas thought to house concrete object representations showed adaptation with repeated presentation of these visually presented objects (for a review, see Grill-Spector et al, 2006;Krekelberg et al, 2005). Recently, however, we showed that adaptation effects are not restricted to simple perceptual representations in visual brain areas, but that, in a very similar fashion, different parts of the cognitive control network showed adaptation to abstract task set representations (De Baene et al, 2012). We demonstrated that the activation difference between switch and repetition trials in task preparation is due to adaptation of abstract task set representations in repeat trials rather than an additional reconfiguration process in switch trials.…”
Section: Introductionmentioning
confidence: 67%
“…In a previous study (De Baene and Brass, 2011), we showed that the fronto-parietal areas displaying preparatory activity in task-switching paradigms (which were also found here) did not show higher activation for cue-switch compared to cue-repeat trials when the task itself was repeated suggesting that these areas do play a role in task set preparation but not in cue-encoding. Furthermore, in another study (De Baene et al, 2012), we have shown that the areas involved in task set preparation do show adaptation to the abstract representation of the task set, but not necessarily to the low-level visual representation of the cue. In this study, we did also show that the higher activation in switch compared to repeat trials in task switching is not related to higher activation in switch trials caused by additional processing to reconfigure the cognitive system for proper task execution but is related to decreased brain activation in repeat trials caused by adaptation to the abstract task representation.…”
Section: Integrating What and Howmentioning
confidence: 76%
See 1 more Smart Citation
“…Thereafter a blank screen was presented for a variable time. Importantly, to be able to disentangle the brain signal associated with the presentation of cue1 from that of cue2 this interval was jittered in a pseudo logarithmic fashion (for a similar procedure see De Baene et al, 2012;Hartstra et al, 2011). Using steps of 600 ms, 50% of the trials used a jitter ranging from 200 to 2000 ms, 33.3% of the trials used a jitter ranging from 2600 to 4400 ms and 16.7% of the trials used a jitter ranging from 5000 to 6600.…”
Section: Designmentioning
confidence: 99%